Evaluating the performance of stock portfolios using the Treynor model applied to the shares of a sample of companies listed in the Iraq Stock Exchange for the period 2005-2013 - Hala Sami Khader Al-Bujari; Ammar Shahab Ahmed Al-Ahmad (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This research aims to highlight the importance of the role of the stock market in the economies of developed and developing countries as the tool that drives the economy towards comprehensive economic development. It plays an important role in financial intermediation between surplus and fiscal deficit units. Affect the investment decisions of investors, which keeps them away from the market due to the lack of differentiation between good and non-good investments, so it was necessary to provide Models or theories that show financial investors how to choose their best investments and thus return to investing in the stock market. One of these models used by investors is the Trainor model, based on the assumption that diversified financial portfolios lead to the elimination of irregular risks and systemic risk Which are measured using a beta coefficient as a measure of portfolio risk and thus evaluate their performance and choose the best one.